Pengambilan Keputusan Investasi Portofolio : Pendekatan Model Indeks Tunggal Saham - Sriyono - Sriyono; Detak - Prapanca; Adelia - Oktaviani (Benefit: Jurnal Manajemen dan Bisnis, 2021)
Abstract. This study aims to determine the composition of the optimal portfolio formation using the Single Index method on LQ-45 shares in the Indonesia Stock Exchange period 2016 - 2018. This research was conducted on the basis of the increasing number of investors who chose to invest their funds in shares, where this is indicated from the increasing positive sentiment on stock investment compared to other investments. Portfolio formation using the Single Index model is one model that can be used to form optimal portfolios, because with this model portfolios are easily formed to fit the desired investment characteristics and objectives to be achieved. The Single Index method is a method that formulates the existence of elements of return and risk in an investment, where the risk element can be minimized through diversification and combining various investment instruments into a portfolio. By using the Single Index method, investors can take advantage of all available information as the basis for maximizing portfolio formation. The sample selection technique of this study used a purposive sampling method and 19 LQ-45 Index stocks were obtained which were used as the research sample. Based on the results of research to determine the optimal portfolio of shares using the Single Index method shows that the LQ-45 Index Shares that form the optimal portfolio are INCO, BBTN, ICBP, INTP, BMRI, BBNI, BBCA, HMSP, INDF shares , GGRM and TLKM. And this study produced 55 portfolio combinations in which there is one efficient portfolio, 26 portfolios with the same funding weight (50%: 50%). Investors choose an efficient portfolio in accordance with the preferences of the level of profit and risk they bearKeywords - Single Index Model, Optimal Portfolio, Expected Return, LQ-45